Functional variants of hepatocyte growth factor identified in patients with adolescent idiopathic scoliosis. Issue 10 (30th May 2019) - Meng, Yichen; Ma, Jun; Lin, Tao; Jiang, Heng; Wang, Ce; Yang, Fu; Zhou, Xuhui
Abstract: The genetic etiology of adolescent idiopathic scoliosis (AIS) remains obscure. Whole‐genome sequencing was performed in four members of one family. Then, we performed a rigorous computational analysis to determine the deleterious effects of the identified variants. Furthermore, the structural differences between the native hepatocyte growth factor (HGF) protein and a protein encoded by an HGF variant containing one mutation (p.T596M) were analyzed using molecular dynamic stimulation. A novel heterozygous mutation (p.T596M) within the HGF gene was identified and found to cosegregate with scoliosis phenotypes in three affected family members. Subsequent modeling and structure‐based analyses supported the theory that this mutation is functionally deleterious. Functional analyses demonstrated that the HGF p.T596 M mutation changed the ability of the HGF protein to be secreted and impaired migration and invasion in HEK293T cells. Furthermore, an HGF knockdown zebrafish model exhibited a curly tailed phenotype. Mutation in HGF is associated with an autosomal dominant pattern of inheritance of AIS. This finding increases our understanding of the genetic heterogeneity of AIS. Abstract : Adolescent idiopathic scoliosis (AIS) is a common spinal deformity without known etiology. In this study, we identified mutations in genes encoding components of the hepatocyte growth factor pathway are associated with an autosomal dominant pattern of inheritance of AIS. This finding provides clues in the understanding of the genetic heterogeneity of AIS.